8-channel logic analyzer controller design FPGA work in progress - Nor Zaidi , Haron; Amir Shah, Abdul Aziz; Masrullizam, Mat Ibrahim; Sani Irwan, Md Salim (2007)
This paper presents a Field Programmable Gate Array (FPGA) based logic analyzer controller. The controller circuit is capable of performing data acquisition and signal display on a 600x480 VGA monitor. The controller was designed using Very High Speed Integrated Circuit Hardware Description Language (VHDL) coding and schematic capture. For validation, behavioral simulations are carried out using Xilinx ISE simulator. The synthesis of the controller onto Xilinx Spartan XC3S200-4FT256 FPGA chip is also presented. The motivation of this project is to explore the capability of designing a complete digital system in a single FPGA chip.